Study of performance of rice with system draper heads - Hidalgo, Ramón; Pozzolo, Oscar; Serafini, Emiliano; Domínguez, Fabio; Beltramino, Julio; Botta, Guido (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
In a rice establishment of the province of Corrientes was evaluated an axial combine equipped with a head of 25 feet draper system. Four treatments were carried on: head 625D Combine at 3 km/h (T1), at 3.5 km/h (T2), 4 km/h (T3) and 4.5 km/h (T4). The variables under study were grain losses, grain mechanical damage and noise. Mechanical damage was determinated in four locations: draper, auger feeders axial cylinder, grain wheel and grain tank. The determination of noise was with standards suggested by the Institute of Rural Engineering INTA Castelar. Conclusions: 1) Damage to the grain is primarily responsible auger feeder mechanism. 2) The draper was working efficiently with minimal damage. 3) Feeding systems (head) and the axial threshing showed no saturation even at the highest speeds of 4.5 km / h. 4) From the 3.2 km / h the system of separation and cleaning began to show saturation. 5) The sound inside the cabin was not over the standards.